Repairing Organisational Legitimacy : the Case of the New Zealand Police - Grant Samkin; Cliff Allen; Kristin Wallace (Australasian Accounting, Business and Finance Journal, 2010)
This paper illustrates how the New Zealand Police use non-financial annual report disclosures in response to adverse media publicity. This longitudinal case study spans the reporting periods ending 30 June 2000 through to 30 June 2007. It involves a detailed examination of the narrative disclosures and images contained in the annual reports, including the Commissioner’s Overview and the Outcome Reports during this time. Three controversial items covered by the media were traced through the annual reports to establish whether the New Zealand Police use image repair discourse supplemented by semiotics in non-financial annual report disclosures to repair organisational legitimacy. The analysis found that non-financial disclosures together with image repair discourse strategies were used by the New Zealand Police, a public sector agency, to repair organisational legitimacy. This paper provides a valuable contribution to researchers and practitioners as it extends the understanding of how public sector agencies use non-financial annual report disclosures.
Keywords: Image repair; Police; Legitimacy; Accountability; Non-financial reporting; Public sector